2022
DOI: 10.1002/eqe.3783
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the site dependency of fragility functions in risk‐targeted design

Abstract: In the ongoing quest for improved seismic design codes, there is currently substantial focus on risk‐targeted design, which aims to achieve more uniform seismic risk across code‐compliant buildings. Such an approach has already been adopted in ASCE 7, which uses lognormal fragility functions, with a single assumed value for dispersion, to generate uniform risk spectra. One challenge to this approach is that fragility functions have been shown to vary depending on the site being considered. This article, theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Fox et al suggested that the fragility will also depend on the location within New Zealand, not just the design, due to the regional variation in ground motion characteristics. 20 While this study assumes that the distribution of fragilities does not vary by location, this regional effect could be included once there are simplified recommendations on how to account for it. The dashed black line represents an aggregated fragility curve across the as-built designs.…”
Section: Selecting a Design Fragilitymentioning
confidence: 99%
“…Fox et al suggested that the fragility will also depend on the location within New Zealand, not just the design, due to the regional variation in ground motion characteristics. 20 While this study assumes that the distribution of fragilities does not vary by location, this regional effect could be included once there are simplified recommendations on how to account for it. The dashed black line represents an aggregated fragility curve across the as-built designs.…”
Section: Selecting a Design Fragilitymentioning
confidence: 99%
“…Thus, this approach assumes an idealized fragility and does not address performance objectives corresponding to non‐collapse. The issue of assuming fixed dispersion and its repercussions on the risk‐targeted design, as in Luco et al., 35 was investigated in great detail by Fox and O'Reilly 41 . Žižmond and Dolšek 28 proposed a seismic action for force‐based design.…”
Section: Introductionmentioning
confidence: 99%
“…The issue of assuming fixed dispersion and its repercussions on the risk-targeted design, as in Luco et al, 35 was investigated in great detail by Fox and O'Reilly. 41 Žižmond and Dolšek 28 proposed a seismic action for force-based design. Seismic loss estimation was further integrated into the process.…”
Section: Introductionmentioning
confidence: 99%
“…The topic of design methods alone occupies one‐third of the papers, which is not surprising given the scope of the SI. The papers by Ahmadie Amiri and Estekanci, 11 Chen et al., 12 and the two by Dolsek and co‐workers, 13,14 deal with the risk‐targeted design of specific structural types, while those of Fox and O'Reilly, 15 Kourehpaz et al., 16 Clemett et al., 17 and Hulsey et al., 18 with the role of seismic vulnerability (i.e., fragility) in risk‐targeted design. A few papers deal with more specific issues, such as non‐structural elements (i.e., Merino et al.…”
mentioning
confidence: 99%